Cognitive Impairment in Tuberculous Meningitis. (20th October 2022) - Davis, Angharad G; Dreyer, Anna J; Albertyn, Christine; Maxebengula, Mpumi; Stek, Cari; Wasserman, Sean; Marais, Suzaan; Bateman, Kathleen; Solms, Mark; Joska, John; Wilkinson, Robert J; Nightingale, Sam
Abstract: Background: Cognitive impairment is reported as a common complication in adult tuberculous meningitis (TBM), yet few studies have systematically assessed the frequency and nature of impairment. Moreover, the impact of impairment on functioning and medication adherence has not been described. Methods: A cognitive test battery (10 measures assessing 7 cognitive domains) was administered to 34 participants with human immunodeficiency virus (HIV)–associated TBM 6 months after diagnosis. Cognitive performance was compared with that a comparator group of 66 people with HIV without a history of tuberculosis. A secondary comparison was made between participants with TBM and 26 participants with HIV 6 months after diagnosis of tuberculosis outside the central nervous system (CNS). Impact on functioning was evaluated, including through assessment of medication adherence. Results: Of 34 participants with TBM, 16 (47%) had low performance on cognitive testing. Cognition was impaired across all domains. Global cognitive performance was significantly lower in participants with TBM than in people with HIV (mean T score, 41 vs 48, respectively; P < .001). These participants also had lower global cognition scores than those with non-CNS tuberculosis (mean global T score, 41 vs 46; P = .02). Functional outcomes were not significantly correlated with cognitive performance in the subgroup of participants in whom this was assessed (n = 19). Conclusions: Low cognitive performance following HIV-associated TBM is common. This effect is independent of, and additional to, effects of HIV and non-CNS tuberculosis disease. Further studies are needed to understand longer-term outcomes, clarify the association with treatment adherence, a key predictor of outcome in TBM, and develop context-specific tools to identify individuals with cognitive difficulties in order to improve outcomes in TBM. Abstract : Cognitive impairment following tuberculous meningitis is poorly described. In a case control study we demonstrate that low cognitive performance affects ∼50% of patients at 6 months following diagnosis HIV-associated TBM, and is significantly worse than that seen in HIV alone